ANALYSIS OF CODE-MIXING TYPES AND MOTIVATIONS ON @IDEXTRATIME TWITTER ACCOUNT (SOCIOLINGUISTIC APPROACH) - Arini Hidayah; Fransiscus Xaverius Bintang Krisna Haryadi (Acceleration: Multidisciplinary Research Journal, 2026)
This study aims to examine the types and reasons for code mixing used in the @idextratime (Extra Time Indonesia) Twitter account. This research employs a descriptive qualitative approach within a case study design, focusing on a football-related social media account. Twitter was selected as the data source due to its high engagement in sports discourse and its tendency to encourage informal bilingual language use. The data consist of 50 utterances containing code-mixing elements, collected through documentation techniques in the form of screenshots. The data were analyzed using data reduction, classification, and interpretation based on Muysken’s (2000) framework of code-mixing types and Hoffman’s (1991) framework of code-mixing motivations. The findings reveal three types of code mixing: insertion (40 occurrences), alternation (3 occurrences), and congruent lexicalization (7 occurrences), with insertion as the dominant type. In terms of reasons, talking about a particular topic is the most frequent (24 occurrences), followed by real lexical need (13 occurrences). The findings indicate that code mixing is primarily used to facilitate effective communication in football discourse, where English terminology is widely recognized.